Kids Take Over the Vancouver Art Gallery - Rome, Susan; Smith, Margo (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
In the spring of 2022, the Vancouver Art Gallery presented an exhibition titled Kids Take Over, which was the result of a collaboration between the education and curatorial departments. Using a variety of gallery education techniques, the Program Coordinator for Schools and Youth worked with children and youth to respond to works from the gallery collection. These responses, along with photos and student artwork, were displayed in the exhibition. This paper presents an overview and reflection on the project. Interviews with those that participated in Kids Take Over demonstrate the positive impact the project had on everyone involved. Several recommendations for other galleries and classroom educators are discussed.